Improving the Quality of Student Education: The Effectiveness of the Interactive Comic 'Besok Aja Deh' in Addressing Academic Procrastination - Yusti, Dini Ananda; Zenmira, Kharisma Nanda (CV. Bimbingan Belajar Assyfa, 2025)
(Background) Time management is a significant challenge among college students, who often face heavy academic, work, and organizational workloads, triggering academic procrastination—the deliberate delay in completing assignments. This behavior directly negatively impacts the quality of learning and the achievement of academic goals, necessitating creative and relevant educational interventions. (Objective) This study aims to test the effectiveness and feasibility of the interactive comic titled